Enabling and Constraining Factors to Knowledge Sharing Among Academicians - Ismail, Fadillah (Research in Management of Technology and Business, 2020)
Knowledge sharing management is an ideal and effective strategy which has become a culture of successful organizational practice. However, most organizations including public sector fail and pay less attention in managing assets i.e. human capital skills and knowledge. Hence this study was conducted to identify the determining factors that influence the sharing of knowledge that occurs successfully among academics in higher education’s institutions. This study obtained information through secondary data. Based on published data, study identifies and lists four key critical factors that lead to the survival of an organization facing challenges and risks. The effective management of knowledge has been described as a critical ingredient for organization seeking to ensure sustainable strategic competitive advantage. Therefore, creating, managing, sharing and utilizing knowledge effectively is vital for organizations to take full advantage of the value of knowledge.